How long does it take to become an entrepreneurial society: The case of german convergence in self-employment - Yvonne Schindele (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Since the beginning of the transformation of East Germany from a socialist planned economy to a market economy, there has been an ambitious political goal of fostering entrepreneurial activity in that part of the country. One of the most-hoped for results of this undertaking is the anticipated contribution of small and new firms to solving the economic, social, and political problems of East Germany, thereby narrowing the gap between East and West Germany. This paper uses panel data from 1992 to 2005 on 97 German regions to analyze recent convergence in self-employment rates. An astonishing catching-up process is observed for East German regions during the period under study. However, the general convergence between East and West Germany observed during the first years after reunification has not been maintained. In short, some East German regions have achieved convergence with West German self-employment rates and some have not.
Keywords: L26; M13; O1; O18; O47; R11; 330; Entrepreneurship; regional convergence; self-employment; regional development; transition; Germany; Unternehmer; Selbstständige; Regionale Entwicklung; Entwicklungskonvergenz; Neue Bundesländer; Alte Bundesländer; Deutschland